PENGARUH METODE OUTDOOR STUDY DENGAN MEMANFAATKAN LINGKUNGAN SEKITAR TERHADAP HASIL BELAJAR SISWA KELAS XI IPS DI SMA NEGERI 5 TAKENGON PADA MATERI KERAGAMAN BUDAYA INDONESIA - Ningrum, Dini Amalia; Desfandi, Mirza; Ruliani, Ruliani (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
ABSTRACKIn essence, education is a right of every individual child nation to be able to enjoy it. Everyone needs education from birth to develop the potential that exists in humans, become a person of knowledge, creativity, and noble character. The purpose of this study was to see the learning outcomes of students at SMA Negeri 5 Takengon using the outdoor study method. This research is an experimental study with a pre-test post-test control group design. The study population was all students of class XI social studies SMA Negeri 5 Takengon which amounted to 48 students with a sample of two classes (experimental class and control class) of which each class numbered 24 students. Data collection is carried out using instruments in the form of tests with a total of 20 questions. Based on the results of the study, it is known that the data of counting = 2.24 while ttabel = 1.678 was obtained. So the result of counting ttabel or 2.24 1.678 means that Ha is accepted and Ho is rejected. So the hypothesis in this study states that the understanding of students taught by the outdoor study method is better than the understanding of students taught conventionally. Based on the results of hypothesis testing, it can be said that in the teaching and learning process by utilizing the surrounding environment so that it can motivate, and increase students' understanding of learning materials. With outdoor learning activities, the learning atmosphere becomes varied and not boring. In addition, students are trained to work together, interact well with each other during discussions, and are able to solve problems.Keywords: Method, Outdoor Study, Utilization of the Surrounding Environment, Learning Outcomes